Improve intra‐uterine insemination in rabbits using ultra‐high temperature skim milk as extender to keep semen at room temperature. (3rd June 2015) - Hozbor, F.; Ledesma, A.; Manes, J.; Ríos, G. L.; Kaiser, G.; Cano, A.; Luciano, C.; Alberio, R.
Summary: Two experiments were carried out to examine in vitro quality and in vivo fertility of rabbit semen diluted in ultra‐high temperature (UHT) skim milk. In the first experiment, pooled ejaculates of 10 adult rabbits were divided in three aliquots. Each aliquot was diluted in saline solution, TrisC or UHTm extender and kept at room temperature for 24 h. Sperm quality assessment was performed during all the incubation periods. In the second experiment, 27 adult rabbit does were inseminated with semen incubated for 5 h. Embryo recovery was performed 96 h after insemination. Results showed that treatments diluted in UHTm registered the highest values of spermatozoon with total motility, intact and functional plasma membrane and greater number of embryos recovered in rabbit does. We conclude that UHT skim milk would be a good extender for improved intra‐uterine insemination in rabbits and to keep sperm cells for several hours at room temperature.